Karakteristik Tindak Pidana dalam Statuta ICC dan Dampak Pembentukan Pengadilan Pidana Internasional (ICC) terhadap Perkembangan Hukum Pidana - Atmasasmita, Romli (UI Scholars Hub, 2021)
International community has emphasized their commitment to combat “the most serious crime of the concerns to the international regarding the nature and the characteristic of such crimes that are often misunderstood amongst the professionals in Indonesian criminal law. Those differences lead to subsequent conquences on state’s criminal jurisdiction, particularly after considering the trans-boundary nature of such crime. The establishment of the International Criminal Court has created a new legal institution in international criminal law. It has reflected a significant change of criminal law that have been recognized since the 18th century.